2021
DOI: 10.1093/oep/gpab009
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal policy uncertainty and its effects on the real economy: German evidence

Abstract: This article introduces a new measure of fiscal policy uncertainty (FPU) based on the disagreement among professional forecasters. We analyse different patterns of this measure for the German economy and also use Italian data for comparison. Especially, we examine the impact of the introduction of the German ‘debt brake’ on FPU. Finally, we conduct an impulse response analysis to investigate the effect of FPU on the real economy and we provide robust evidence that FPU significantly decreases the growth rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This implies that the uncertainty about the current year naturally decreases over time (e.g., it is much lower in November than in January). Therefore, to transform fixed event into fixed horizon forecasts, we apply the weighted averaging approach established by Patton and Timmermann (2011) and used in the related literature since then (Beckmann & Czudaj, 2018, 2021; Dovern et al, 2012). The simple idea is to use the weighted average of fixed event forecasts for the current truef^1,0 and the next year truef^2,1 with the weight ω of the former (latter) linearly decreasing (increasing) as time evolves.…”
Section: Datamentioning
confidence: 99%
“…This implies that the uncertainty about the current year naturally decreases over time (e.g., it is much lower in November than in January). Therefore, to transform fixed event into fixed horizon forecasts, we apply the weighted averaging approach established by Patton and Timmermann (2011) and used in the related literature since then (Beckmann & Czudaj, 2018, 2021; Dovern et al, 2012). The simple idea is to use the weighted average of fixed event forecasts for the current truef^1,0 and the next year truef^2,1 with the weight ω of the former (latter) linearly decreasing (increasing) as time evolves.…”
Section: Datamentioning
confidence: 99%
“…The study revealed that, when compared to fiscal policy, monetary policy via exchange rate was more successful in promoting growth. Beckmann and Czudaj (2021) used Italian data to compare alternative patterns of fiscal policy uncertainty (FPU) for the German economy. The influence of Germany's 'debt brake' on the FPU.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fiscal policy is an important economic policy and the main tool for the government to guide the development of companies. Studies have shown that fiscal policy uncertainty has a profound impact on the development of the real economy (Beckmann & Czudaj, 2021). This paper analyzes the possible impact of fiscal policy uncertainty on corporate decision‐making and growth and expands the theoretical research on China's economic policy uncertainty from the perspective of fiscal policy.…”
Section: Introductionmentioning
confidence: 99%